CLINICAL OUTCOMES AFTER MEDIAL PATELLOFEMORAL LIGAMENT RECONSTRUCTION UTILIZING ALLOGRAFT TISSUE IN PEDIATRIC AND ADOLESCENT PATIENTS: MINIMUM 2-YEAR FOLLOW-UP. Issue 7 (30th July 2021) - Allahabadi, Sachin; Pandya, Nirav K.
Background: Medial patellofemoral ligament (MPFL) reconstruction has gained popularity as a tool to manage recurrent patellar instability. The use of allograft for reconstruction includes benefits of quicker surgical time and obviating donor-site morbidity. In anterior cruciate ligament (ACL) reconstruction hesitancy exists to use allograft in younger patients based on data demonstrating higher graft failure rates. However, a similar trend of allograft failure has not been demonstrated for reconstruction of the MPFL, which has a lower tensile strength than that of the ACL. Hypothesis/Purpose: The purpose of this study is to evaluate outcomes including recurrent instability after MPFL reconstruction utilizing allograft tissue in pediatric and adolescent patients. Methods: A retrospective review was performed to identify patients of a single surgeon with MPFL reconstructions with allograft for recurrent patellar instability with minimum two-year follow-up. Surgical management was recommended after minimum six weeks of nonoperative management including bracing, physical therapy, and activity modification. Pre-operative x-rays were evaluated to assess physeal closure, lower extremity alignment and trochlear morphology, and Insall-Salvati and Caton-Deschamps ratios. MRIs were reviewed to evaluate the MPFL, trochlear morphology, and tibial tubercle trochlear groove distance (TT-TG). The allograft was fixed with a bioabsorbable screw. Descriptive statistics were used to characterize data. The primary outcome was recurrent instability. Results: 20 patients (23 knees) 14 females (17 knees) with average age 15.8 years (range: 11.5-19.6 years) underwent MPFL reconstruction with allograft with average follow-up of 3.6 years (range: 2.2-5.9 years). Physes were open in 8 knees. Average Insall-Salvati ratio was 1.08 ± 0.16 and Caton-Deschamps index was 1.18 ± 0.15. Eighteen patients were noted to have trochlear dysplasia pre-operatively and TT-TG was 15.4 ± 3.9 mm. The three knees (13.0%) with complications had open physes – two (8.7%) had recurrent instability requiring subsequent operation and one sustained a patella fracture requiring open reduction internal fixation. The average Insall-Salvati of these three patients was 1.26 ± 0.21, Caton-Deschamps was 1.18 ± 0.21, and TT-TG was 18.3 ± 3.5mm. There were no growth disturbances noted post-operatively. Conclusion: MPFL reconstruction using allograft tissue may be performed safely in the pediatric and adolescent population with good outcomes at mid-term follow-up with few complications and low rate of recurrent instability. Anatomic factors for may contribute to recurrent instability and complications post-operatively, though larger numbers are needed for statistical analyses. Further prospective and randomized evaluation comparing autograft to allograft reconstruction is warranted to understand graft failure rates.